Control Chart in Microbiological Cleaning Efficacy of Pharmaceutical Facility - Eissa, Mostafa Essam; Mahmoud, Ahmed Mohamed; Nouby, Ahmed Saber (Dhaka University Journal of Pharmaceutical Sciences, 2016)
Statistical process control and quality control charts have important applications in the field of microbiological quality control of clean area. Monitoring the environment and the surface samples using contact plates is critical to verify microbiological cleaning efficacy of the surface and to understand the behavior of the operation. In the current study, RODAC (Replicate Organism Detection and Counting) plates were used to sample surfaces in production rooms for semisolid and liquid products in a course of two years and overall performance was assessed using I-MR chart and data were subjected to analysis. The throughput yield (TPY) was 0.999993 and the overall process capability was acceptable (Ppk was 1.45). The used methodology in microbiological quality control is simple, fast and not expensive, which provides insight for the evaluation of the process efficiency and highlights the limiting factors and the drawbacks that affect the performance. Dhaka Univ. J. Pharm. Sci. 14(2): 133-138, 2015 (December)